Comparison of the WASPAS and MOORA Methods in Providing Single Tuition Scholarships - Nelly Khairani Daulay; Bunga Intan; Muhammad Irvai (The IJICS (International Journal of Informatics and Computer Science), 2021)
Single Tuition Scholarship (UKT) is a grant provided by the Ministry of Education and Culture (Kemendikbud) to universities, both State Universities (PTN) and Private Universities (PTS). This aims to help underprivileged people so they can get education in higher education, both PTN and PTS. The large number of UKT recipient participants overwhelmed the University and made the decision not objective. For this reason, it is necessary to have a decision support system (SPK) in order to help deal with these problems. There are many methods that can be used in SPK including the MOORA method, WASPAS, TOPSIS, SAW, WPS and many more. In this study, researchers tried to compare two methods between the WASPAS method and the MOORA method in determining UKT scholarship recipients. There are five criteria for selecting recipients of UKT assistance, namely parents' income, electricity bills, water bills, land and building taxes and family expenses. The results of this study were students who got the first rank with the WASPAS method, namely 4,152 and students with the MOORA method, namely 3,218. This shows that these students are entitled to receive UKT grants